Benchmarking of abdominal surgery: a study evaluating the HARM score in a European national cohort. Issue 4 (21st April 2020) - Helgeland, J.; Skyrud, K.; Lindahl, A. K.; Keller, D.; Augestad, K. M.
Abstract : Background: Reliable, easily accessible metrics of surgical quality are currently lacking. The HARM (HospitAl length of stay, Readmission and Mortality) score is a composite measure that has been validated across diverse surgical cohorts. The aim of this study was to validate the HARM score in a national population of patients undergoing abdominal surgery. Methods: Data on all abdominal surgery in Norwegian hospitals from 2011 to 2017 were obtained from the Norwegian Patient Registry. Readmissions and 30‐day postoperative complications as well as deaths in and out of hospital were evaluated. The HARM scoring algorithm was tested after adjustment by establishing a newly proposed length of stay score. The correlation between the HARM score and complications, as well as the ability of aggregated HARM scores to discriminate between hospitals, were analysed. Risk adjustment models were developed for nationwide hospital comparisons. Results: The data consisted of 407 113 primary operations on 295 999 patients in 85 hospitals. The HARM score was associated with complications and complication severity (Goodman–Kruskal γ value 0·59). Surgical specialty was the dominating variable for risk adjustment. Based on 1‐year data, the risk‐adjusted score classified 16 hospitals as low HARM score and 16 as high HARM score of the 53 hospitals that had at least 30 operations. Conclusion: The HARM score correlates with major outcomes and is associated with the presence and severity of complications. After risk adjustment, the HARM score discriminated strongly between hospitals in a European population of abdominal surgery. Abstract : The HARM score, calculated from length of stay, readmissions and postoperative mortality, was studied in a national gastrointestinal surgical population. It was found to be associated with complications and could differentiate between hospitals. benchmark in abdominal surgery Abstract : Antecedentes: En la actualidad no se dispone de un sistema de cuantificación numérica confiable y accesible para evaluar la calidad quirúrgica. La puntuación HARM es una medida compuesta basada en la duración de la estancia hospitalaria, los reingresos y la mortalidad postoperatoria que se ha validado en varias cohortes quirúrgicas. El objetivo de este estudio fue validar la puntuación HARM en una población nacional de pacientes sometidos a cirugía abdominal. Métodos: Se obtuvieron los datos de todas las cirugías abdominales realizadas en hospitales noruegos entre 2011 y 2017 a través del registro noruego de pacientes. Se evaluaron los reingresos y las complicaciones postoperatorias a los 30 días, así como la mortalidad intra‐ y extra‐hospitalaria. Se utilizó el algoritmo de puntuación HARM tras el ajuste con la nueva propuesta de puntuación para la duración de la estancia hospitalaria. Se analizó la correlación entre HARM y complicaciones, así como la capacidad de las puntuaciones HARM agregadas para discriminar entre hospitales. Se desarrollaron modelos de ajuste de riesgo para las comparar hospitales en todo el país. Resultados: Se incluyeron 407.113 intervenciones primarias llevadas a cabo en 295.999 pacientes en 85 hospitales. La puntuación HARM se asoció con las complicaciones y la gravedad de la complicación (Goodman‐Kruskal γ de 0, 59). La especialidad quirúrgica fue la variable dominante para el ajuste del riesgo. Utilizando los datos de un período anual, la puntuación ajustada al riesgo clasificó a 16 hospitales como de baja puntuación y a 16 de alta puntuación de los 53 hospitales en los que se habían realizado al menos 30 intervenciones. Conclusión: La puntuación HARM se correlaciona con los resultados principales y con la presencia y la gravedad de las complicaciones. La puntuación HARM, después del ajuste de riesgo, discrimina de forma sólida entre hospitales en una población europea de cirugía abdominal. This article is protected by copyright. All rights reserved.